2019
DOI: 10.1108/md-01-2019-0058
|View full text |Cite
|
Sign up to set email alerts
|

Do stakeholder relationships matter? An empirical study of exploration, exploitation and firm performance

Abstract: Purpose The purpose of this paper is to investigate the performance implications of two major mechanisms for organizational learning (i.e. exploration and exploitation). Exploration refers to firm activities that explore new and novel knowledge, whereas exploitation reflects the extent to which a firm reuses its existing knowledge. The authors predict curvilinear (i.e. an inverted U-shape) relationships between exploration/exploitation and firm performance, respectively. That is, firm performance first increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 112 publications
0
25
0
Order By: Relevance
“…Only three studies have discussed the effect of managing for external stakeholders (MES) on exploitative and exploratory innovation separately: Two inductive studies both argued that MES stakeholders could be beneficial for both types of innovation (Kazadi et al, 2016;Partanen et al, 2014). In the only deductive analysis of the relationships so far, Zhao et al (2021) made similar arguments but found no empirical support for either relationship.…”
Section: Dimensions Of Managing For Stakeholders and Innovationmentioning
confidence: 99%
“…Only three studies have discussed the effect of managing for external stakeholders (MES) on exploitative and exploratory innovation separately: Two inductive studies both argued that MES stakeholders could be beneficial for both types of innovation (Kazadi et al, 2016;Partanen et al, 2014). In the only deductive analysis of the relationships so far, Zhao et al (2021) made similar arguments but found no empirical support for either relationship.…”
Section: Dimensions Of Managing For Stakeholders and Innovationmentioning
confidence: 99%
“…(2) Based on the perspective of organizational learning, it is believed that learning is an important way for enterprises to acquire and use knowledge, and the key is on how to balance different aspects of organizational learning (Kim et al. , 2012; Luo, 2000; Zhao et al. , 2019).…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%
“…Organizational learning, as an essential means of knowledge acquisition, sharing and utilization, can help corporations reduce the effect of external environments (Luo, 2000) and provide crucial value for foreign subsidiary performance (Barkema et al. , 1996; Zhao et al. , 2019).…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%
See 2 more Smart Citations